1997
DOI: 10.1099/00221287-143-7-2457
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Sck1 is involved in trehalase activation by glucose and nitrogen source in the fission yeast Schizosaccharomyces pombe

Abstract: Summary: Trehalase activity is markedly enhanced upon addition of glucose and a nitrogen source to cells of the fission yeast Schizosaccharomyces pombe. This increase corresponds to a post-translational activation of the enzyme, which is controlled by cAMP-dependent and cAMP-independent pathways. Recent work has shown that overexpression of SCK1 in Schiz. pombe is able to suppress mutations that result in reduced Pka1 (cAMP-dependent protein kinase A activity, suggesting that Sck1 (suppressor of loss of cAMP-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…Several reports have shown that trehalase can be posttranslationally activated in this yeast by enzyme phosphorylation (Soto et al, 1997). Thus, we investigated whether the increase in trehalase induced by oxidative stress could be due, at least in part, to modification of the enzyme protein by phosphorylation.…”
Section: Evidence For Activation and Induction Of Trehalase By Oxidatmentioning
confidence: 98%
“…Several reports have shown that trehalase can be posttranslationally activated in this yeast by enzyme phosphorylation (Soto et al, 1997). Thus, we investigated whether the increase in trehalase induced by oxidative stress could be due, at least in part, to modification of the enzyme protein by phosphorylation.…”
Section: Evidence For Activation and Induction Of Trehalase By Oxidatmentioning
confidence: 98%
“…In the absence of such "extra" phosphatase activity, ⌬tpp1 spores should be phenotypically similar to ⌬tps1 spores (4), i.e., unable to mobilize trehalose and therefore unable to germinate, since neutral trehalase of S. pombe does not recognize trehalose-6P as a substrate (data not shown). Besides, all the known routes for neutral trehalase activation previously described in S. pombe (8,10,24,25,27) were shown to be fully functional in ⌬tpp1 strains, which is clearly different from ⌬tps1 strains, where neutral trehalase is activated only by osmostress (6).…”
Section: Properties Of Tpp1mentioning
confidence: 99%
“…Thus, basal expression of the genes involved in either synthesis or degradation of trehalose appears to be repressed by Pka1 activity. However, in a double disruptant for Pka1 and Sck1 (a protein kinase that supresses some defects of ⌬pka1 mutants and regulates neutral-trehalase activation under different conditions) (17,25), tpp1 ϩ expression recovered the wild-type basal levels (Fig. 3D).…”
Section: Figmentioning
confidence: 99%
“…4). Further support for a downstream role in nutrient signaling by Sck1 and its budding yeast homolog Sch9p comes from studies of trehalose mobilization as a function of nitrogen signaling (27,28). The study of Sch9p identified it as a negative regulator of PKA and the likely target of activation by nitrogen via the fermentable-growth-medium induced pathway (27).…”
Section: Fig 2 Mutations In Git3mentioning
confidence: 99%